Моделирование электротоковых микрореле - Krival, I. I.; Skrypnyuk, A. I.; Protsenko, V. A.; Maryenko, A. V. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
The optimal parameters of UA Ч3-79M and UA Ч3-101 frequency meter’s units such as frequency synthesizer and intermediate frequency amplifier are analised. It is shown that the choice of these units parameters affects the measurement frequency range, accuracy and other characteristics of frequency meters. Operation algorithm of the frequency meter at frequency range up to 40 GHz with changing of sinusoidal frequency and changing carrier frequency radiopulse signals and the recommendations for choosing the optimal parameters are given.